Acute Portal Vein Thrombosis during COVID-19 Convalescent Phase - Rahimian, Shoja; Pawar, Tushar; Garrahy, Ian; Rettew, Andrew (Case Reports in Hematology, 2022)
Acute portal vein thrombosis represents a less common type of venous thromboembolism, even among the prothrombotic complications of coronavirus disease 2019 (COVID-19). Such complications are primarily reported during the active phase of infection. The case here describes acute portal vein thrombosis following resolution of COVID-19 in a 44-year-old male who presented with abdominal pain. Abdominal imaging identified portal and other splanchnic vein thromboses. Studies for hypercoagulable conditions were negative. Polymerase chain reaction was negative for severe acute respiratory syndrome coronavirus-2; however, IgG serology was positive. The case highlights the importance of considering thrombotic complications, particularly splanchnic vein thromboses, in patients with recent COVID-19.